Sociology on the menu : an invitation to the study of food and society - Beardsworth, Alan, 1945-; Keil, Teresa, 1935- (London ; New York : Routledge, 1997)
Sociology on the Menu is an accessible introduction to the sociology of food. Highlighting the social and cultural dimensions of the human food system it encourages us to consider new ways of thinking of the everyday act of eating.
pt. 1. The social dimensions of the food system -- pt. 2. The social organization of eating -- pt. 3. Food, health and well-being -- pt. 4. Patterns of preference and avoidance.
Includes bibliographical references (pages 260-270) and indexes.
Print version record.
eBooks on EBSCOhost
Keywords: Food habits; Food consumption; Nutrition; Food preferences; Sociology; Food Preferences; Sociology; Feeding Behavior; Nutritional Physiological Phenomena; Habitudes alimentaires; Aliments -- Consommation; Nutrition; Préférences alimentaires; Sociologie; sociology; HEALTH & FITNESS -- Beauty & Grooming; Sociology; Food preferences; Food consumption; Food habits; Nutrition